2023
DOI: 10.48095/cccg2023180
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy in a patient with diastasis of the rectus abdominis muscle after childbirth

Abstract: Background: Examination for the presence of diastasis of the rectus abdominis muscle and examination of the entire posture is very important in postpartum women. Currently, examination by 2D ultrasound, caliper and palpation is used. It is examined at rest and during stress tests. Methods: Case study of a patient with diastasis of the direct abdominal muscle after a fi rst spontaneous uncomplicated delivery at the age of 32 years. Examination to confirm diastasis of the rectus abdominis muscle – the width of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…During exercise, adding core movement in addition to abdominal support can effectively treat and help turn off DRA, while also potentially reducing back discomfort caused by DRA. A recent study developed by Rastislav Dudič et al [ 41 ] demonstrated that physical exercise might help to reduce the diastasis of the direct abdominal muscle in postpartum women. The objectification methods included activation of pelvic floor muscles, postural adjustment, and modification of breathing stereotype and quality.…”
Section: Discussionmentioning
confidence: 99%
“…During exercise, adding core movement in addition to abdominal support can effectively treat and help turn off DRA, while also potentially reducing back discomfort caused by DRA. A recent study developed by Rastislav Dudič et al [ 41 ] demonstrated that physical exercise might help to reduce the diastasis of the direct abdominal muscle in postpartum women. The objectification methods included activation of pelvic floor muscles, postural adjustment, and modification of breathing stereotype and quality.…”
Section: Discussionmentioning
confidence: 99%